THE INFLUENCE OF TEAMWORK AS AN INTERNAL MARKETING FACTOR ON THE QUALITY OF THE SERVICE OF INSURANCE COMPANIES: AN ANALYSIS IN THE REPUBLIC OF SERBIASS AGRICULTURAL SECTOR - Piljan, Ivan; Simonovic, Zoran; Ćurčić, Nikola (Economics of Agriculture, 2020)
The subject matter of this paper is the analysis of the quality of the services and the sustainability of the business operations of insurance companies in the agricultural sector in the Republic of Serbia, depending on the teamwork concept. Teamwork belongs to the internal marketing factors in companies business doing. Teams should have a common goal which the members may only achieve through joint work and a combination of the knowledge and abilities pertaining to different areas. Client satisfaction is a teamwork efficiency measure. Apart from a large number of satisfied users, a large number of new insurance programs innovated from year to year and offering its users an increasingly big range of possible types of insurance are also the indicators of the successful business doing of insurance companies in the agricultural sector. The research study was done on a suitable sample of 250 respondents, employed in 10 insurance companies.